DAMPAK SOSIAL EKONOMI DAN LINGKUNGAN TERHADAP KEBIASAAN MASYARAKAT MELAKUKAN BUANG AIR BESAR - Frida Hendrarinata; Ushnida Rohmah; Sunaryo .; Beny Suyanto (Jurnal Hygiene Sanitasi, 2022)
The results of reports from the Ponorogo health office for people who still defecate openly as much as 73.09%. From these data, after the initial survey, there were some people who did not have a latrine and some had a habit of throwing their feces in the river. If this situation continues, it is likely that problems will arise in the community. This study aims to assess the factors that influence open defecation (economic and environmental conditions) in Pulosari Village, Jambon District, Ponorogo Regency. This type of research uses descriptive research with a survey approach. The data collection technique used proportional random sampling technique. Data was collected by means of interviews, observation and documentation with a questionnaire guide. The number of samples is 87 heads of families. The variables assessed were bowel habits, economic and environmental conditions. The data processing method uses descriptive data analysis presented in the form of tables and narratives. The results showed that the value of defecation habits in general was in the bad category (69.65%), the economic condition of the respondents in general was in the poor category (19.25%) and the environment here, namely the distance from the house to the river in general, was in the category bad (50%). The conclusion of the factors that influence the habit of open defecation in Pulosari Village, Jambon District, Ponorogo Regency, are the habits of the people themselves who defecate indiscriminately, the economic level of the community is lacking and the presence of rivers close to their homes.